2014
DOI: 10.4103/0976-237x.128661
|View full text |Cite
|
Sign up to set email alerts
|

A Scanning electron microscopic evaluation of intracanal smear layer removal by two different final irrigation activation systems

Abstract: Aim:The aim of this study was to compare smear layer removal at apical 1 mm level after final irrigation activation with an EndoVac system and Max-I probe.Materials and Methods:Fifty freshly extracted maxillary central incisors were randomly divided into two groups after completing cleaning and shaping with ProTaper rotary files. In one group, final irrigation was performed with an EndoVac system while in the other group final irrigation was performed with a 30 gauge Max-I probe. 3% sodium hypochlorite and 17%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…, Akyuz‐Ekim & Erdemir , Dua et al . ()]. The detailed reasons for rejection of the 21 articles excluded at full‐text evaluation are given in Table .…”
Section: Reviewmentioning
confidence: 99%
“…, Akyuz‐Ekim & Erdemir , Dua et al . ()]. The detailed reasons for rejection of the 21 articles excluded at full‐text evaluation are given in Table .…”
Section: Reviewmentioning
confidence: 99%
“…In this case, a negative‐pressure irrigation system (EndoVac) was used to rinse the canal with bleach. Several studies have demonstrated that when compared with end‐vented and side‐vented endodontic irrigation needles, the EndoVac system extrudes significantly less irrigant solution and removes a greater amount of organic and inorganic debris from the apical third of the root canal 10 11…”
Section: Discussionmentioning
confidence: 99%
“…Teeth were cleaned from soft tissues and calculus using a hand scaler, washed with water then stored in sterile normal saline solution at room temperature which was changed every 24 hours until the teeth were used within three months after extraction [7]. The crowns of all teeth were removed near the level of cementoenamel junction with a diamond disk * attached to a slow speed handpiece * under copious amount of water to obtain approximately 15 ±1 mm uniform root lengths.…”
Section: Sample Collectionmentioning
confidence: 99%